"Exploratory experimentation" as a probe into the relation between historiography and philosophy of science. (February 2016) - Schickore, Jutta
Abstract: This essay utilizes the concept "exploratory experimentation" as a probe into the relation between historiography and philosophy of science. The essay traces the emergence of the historiographical concept "exploratory experimentation" in the late 1990s. The reconstruction of the early discussions about exploratory experimentation shows that the introduction of the concept had unintended consequences: Initially designed to debunk philosophical ideas about theory testing, the concept "exploratory experimentation" quickly exposed the poverty of our conceptual tools for the analysis of experimental practice. Looking back at a number of detailed analyses of experimental research, we can now appreciate that the concept of exploratory experimentation is too vague and too elusive to fill the desideratum whose existence it revealed. Highlights: The essay traces the emergence of the historiographical concept "exploratory experimentation" in the late 1990s. The introduction of the concept "exploratory experimentation" had unintended consequences: The discussion exposed the poverty of our conceptual tools for the analysis of experimental practice. The concept "exploratory experimentation" does not exemplify the convergence of history and philosophy of science but signals the emergence of a new "integrated HPS" community.